Culture, Identity and Learning: A Mediation Model in the Context of Blogging in Teacher Education - Liat Biberman-Shalev; Gemma Tur; Ilona Buchem (Open Praxis, 2019)
National culture has been an influential framework for comparative and international research. However, current theories suggest that people and societies are rather more complex constructs than their cultural layer. This work is based on a previous study in which, when students from Spain were compared to German students, the former showed higher levels of identity with their blogs and learning impact. The current study is a step forward as it presents the differences in identity and learning impact in blogging between Spanish and Israeli student teachers and offers a mediation model in which the relationship between culture and learning is mediated by the identity factor. The results show that Spanish student teachers feel more identified with their blogs and thus perceive a greater learning impact. Accordingly, this work suggests that blogging could act as learning spaces that may raise students’ identity with their learning products and their self-perceived learning impact.